Implemented models and elements for heart failure care in the regions of the Russian Federation: prospects for transformation into regional cardiovascular risk management systems - E. V. Shlyakhto; N. E. Zvartau; S. V. Villevalde; A. N. Yakovlev; A. E. Soloveva; N. G. Avdonina; E. A. Medvedeva; G. V. Endubaeva; V. A. Karlina; A. E. Solovev; A. A. Fedorenko; V. V. Zaitsev; et al. (Российский кардиологический журнал)
The high and growing incidence and mortality of patients with heart failure (HF) should receive priority attention when developing an action plan to reduce cardiovascular mortality in the Russian Federation. The article provides an analysis of the implemented elements of HF care in 40 Russian regions (Northwestern, North Caucasian, Volga, Southern Federal districts), some of the best practices, as well as prospects for implementation of the cardiovascular risk management system.